Acquisition of chromosome instability is a mechanism to evade oncogene addiction. Issue 3 (6th February 2020) - Salgueiro, Lorena; Buccitelli, Christopher; Rowald, Konstantina; Somogyi, Kalman; Kandala, Sridhar; Korbel, Jan O; Sotillo, Rocio
Abstract: Chromosome instability (CIN) has been associated with therapeutic resistance in many cancers. However, whether tumours become genomically unstable as an evolutionary mechanism to overcome the bottleneck exerted by therapy is not clear. Using a CIN model of Kras‐driven breast cancer, we demonstrate that aneuploid tumours acquire genetic modifications that facilitate the development of resistance to targeted therapy faster than euploid tumours. We further show that the few initially chromosomally stable cancers that manage to persist during treatment do so concomitantly with the acquisition of CIN. Whole‐genome sequencing analysis revealed that the most predominant genetic alteration in resistant tumours, originated from either euploid or aneuploid primary tumours, was an amplification on chromosome 6 containing the cMet oncogene. We further show that these tumours are dependent on cMet since its pharmacological inhibition leads to reduced growth and increased cell death. Our results highlight that irrespective of the initial CIN levels, cancer genomes are dynamic and the acquisition of a certain level of CIN, either induced or spontaneous, is a mechanism to circumvent oncogene addiction. Synopsis: Cancer genomes are dynamic, and the acquisition of a certain level of chromosome instability is a source of genetic variability. This study reveals that genetic variability provides mechanisms to resist the strong selective pressure exerted by targeted therapy, and to circumvent oncogene addiction. Chromosomal Instability is a mechanism to circumvent oncogene addiction. Genetic alterations driving resistance were most probably acquired during the course of the treatment. The most predominant genetic alteration in resistant tumors of a Kras‐driven breast cancer mouse model was an amplification of the cMet oncogene. Abstract : Cancer genomes are dynamic, and the acquisition of a certain level of chromosome instability is a source of genetic variability. This study reveals that genetic variability provides mechanisms to resist the strong selective pressure exerted by targeted therapy, and to circumvent oncogene addiction.